In vitro models of xenobiotic metabolism in trout for use in environmental bioaccumulation studies. (1st May 2013) - Uchea, Chibuzor; Sarda, Sunil; Schulz-Utermoehl, Timothy; Owen, Stewart; Chipman, Kevin J.
Abstract : 1. In vitro screens are sought as informative, alternatives to the use of animals in vivo and to improve upon the current use of fish liver 9000 g supernatants (S9) in environmental risk assessment. 2. The rates of ethoxyresorufin- O -deethylation (relative to S9 protein) measured under different conditions of culture of rainbow trout hepatocytes were significantly higher than those detected in S9, in the order of freshly isolated hepatocytes > 10-day spheroid cultures > primary hepatocytes in culture > S9. The percentage of conjugated metabolites was also similar between freshly isolated and spheroid cultured hepatocytes (9.9 and 13.5%). 3. The rate of oxidation was enhanced (1.7 fold) when S9 was supplemented with cofactors for phase II conjugation but this was only approximately one tenth of the rate in freshly isolated hepatocytes (7.1 pmol/min/mg S9 protein equivalent). 4. Hepatocytes also hydroxylated ibuprofen, producing two metabolites, in contrast to only one (identified as the 1-hydroxy derivative) using hepatic S9 fractions. 5. Since the bioaccumulation potential of chemicals is often based on un-supplemented S9 in incubations ≥1 h when activity declines, it is recommended that predictability would be greatly improved through the use of hepatocyte spheroids, due to their maintenance of activity and longevity.